ITECSOL - INCUBADORA DE ECONOMIA SOLIDÁRIA, DESENVOLVIMENTO E TECNOLOGIA SOCIAL DA UNIJUÍ – 2011 - Dellapiane, Julieta; Rasia, Carlos; Basso, Lauri; Silva, Enio W. D.; Barcelos, Eronita S.; Scariot, Nadia (Salão do Conhecimento, 2013)
Resumo